Novel Quantification Method for Lithium Ion Battery Electrolyte Solvents in Aqueous Recycling Samples Using Solid‐Phase Extraction/Gas Chromatography‐Flame Ionization Detection - Julius Buchmann; Yixin Song; Simon Wiemers‐Meyer; Martin Winter; Sascha Nowak (Advanced Energy & Sustainability Research)
Efficient recycling processes of lithium ion batteries are critical for advancing the sustainability of this technology. Yet, the quantitative analysis of potential electrolyte residues in wastewaters generated in the recycling process can be challenging. This study introduces a robust method that combines solid‐phase extraction with gas chromatography‐flame ionization detection for quantifying organic carbonate electrolyte solvents and their degradation products in aqueous samples. A quantitative extraction of all target analytes is achieved using the polystyrene‐divinylbenzene‐based stationary phase LiChrolut EN. Method optimization and limitations are evaluated by varying mass loading, load and elution volume, enabling preconcentration factors >250 for linear and oligomeric carbonates. More hydrophilic cyclic carbonates exhibit lower preconcentration potential due to reduced retention on the cartridge. However, limits of quantification in the water sample in a range of a few hundred ppb are achieved for cyclic carbonates (186 ppb for ethylene carbonate, 119 ppb for vinylene carbonate) and down to the single‐digit ppb range for linear and oligomeric carbonates. Additionally, effective matrix elimination is demonstrated through the removal of ionic compounds, such as conductive salts, while the extraction efficiency is independent of the matrix. In conclusion, a robust quantification method is developed, suitable for monitoring wastewater treatment processes and environmental samples.